5x+5x+7x-3+10x+10x-5x-20=

Simple and best practice solution for 5x+5x+7x-3+10x+10x-5x-20= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+5x+7x-3+10x+10x-5x-20= equation:


Simplifying
5x + 5x + 7x + -3 + 10x + 10x + -5x + -20 = 0

Reorder the terms:
-3 + -20 + 5x + 5x + 7x + 10x + 10x + -5x = 0

Combine like terms: -3 + -20 = -23
-23 + 5x + 5x + 7x + 10x + 10x + -5x = 0

Combine like terms: 5x + 5x = 10x
-23 + 10x + 7x + 10x + 10x + -5x = 0

Combine like terms: 10x + 7x = 17x
-23 + 17x + 10x + 10x + -5x = 0

Combine like terms: 17x + 10x = 27x
-23 + 27x + 10x + -5x = 0

Combine like terms: 27x + 10x = 37x
-23 + 37x + -5x = 0

Combine like terms: 37x + -5x = 32x
-23 + 32x = 0

Solving
-23 + 32x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '23' to each side of the equation.
-23 + 23 + 32x = 0 + 23

Combine like terms: -23 + 23 = 0
0 + 32x = 0 + 23
32x = 0 + 23

Combine like terms: 0 + 23 = 23
32x = 23

Divide each side by '32'.
x = 0.71875

Simplifying
x = 0.71875

See similar equations:

| 9y-4(3y-2)+6(y-3)=32 | | 3x*9=27 | | -13y(-6y+13)-3(16y+11)=39y(2y-10)-8 | | -15y(17y+4)+7=-7(-7y+9)+3y(-85y-4) | | -11(-5x-5)=18(-12x+4)-5x-16(-19x-4)-10 | | 6+3x-2(x+4)=20 | | -9(5y-4)-8+15(10y+11)=8-9(-11y-7) | | 11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10) | | 4/(z+2)-1/(3z+6)=11/9 | | y^4+y^3+2y^2=0 | | 6x+2=5x+6 | | 2x-3/6+3x-2/4+5x+6/12=4 | | 75=3(10t-3)6t | | 2+5x=7+4x | | -x-4=-2x | | -18(13y+12)=-17+16(13y+8)-15(9y+17) | | 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x |

Equations solver categories